Perlindungan Hukum Terhadap Pekerja Toko Karpet di Desa Adat Seminyak (Studi Kasus di Crown Carpets) - Marthen Lazarus Laning; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2024)
Legal protection and liability are important parts of employment. The Indonesian government creates jobs with legal protection for workers based on Pancasila and the 1945 Constitution. The omnibus law version of the Manpower Law explains the protection of workers in realizing welfare. The case study is located at Crown Carpets in Seminyak Traditional Village, Bali. Empirical legal research method with a focus on collecting data directly from the field through observation and interviews. The main source of data comes from employees at Crown Carpets and the owner of the company provides information about the protection and legal liability in the carpet shop. Secondary data includes relevant primary and secondary legal materials. The data analysis technique used is descriptive technique. The results of the interview obtained that the Crown Carpets company's responsibility for its workers only provides compensation based on the employment relationship, without providing adequate protection in accordance with applicable labor regulations. The owner of Crown Carpets revealed that the company only has verbal agreements with its workers, which do not provide definite guarantees related to work safety and financial protection in the case of serious work accidents in the form of insurance.